Analysis of the development trend and key scenarios of smart communities based on 5G+AIoT - Nian TAO; Sheng ZHANG; Tai FU (Dianxin kexue)
With the continuous development and maturity of new-generation information technologies such as 5G, artificial intelligence, and the Internet of things, the construction of smart communities has entered the second half, with greater space and higher requirements.Firstly, the development status of community and business needs was analyzed.Secondly, the design ideas based on “pan-sensing, data collection, and intelligent application” was proposed for the pain points of users, such as government, property management and residents.Thirdly, an overall plan for 5G+AIoT smart community was built, focusing on wisdom community 5G application scenarios, the industrial and social benefits of smart community construction were discussed.Finally, the future development trend of smart communities was looked forward.